Dolores Claiborne - King, Stephen (Viking, 1993)
Did Dolores Claiborne murder her abusive husband on July 20, 1963, the day of a solar eclipse in Maine? Did she push her elderly, ailing employer on a fatal trip down the staircase over 30 years later? As her daughter lies in bed, her mother's voice tells the story of the events that shaped her life.